Bandwidth compression of full parallax holographic stereogram using nonuniform sampling. (4th September 2015) - Pei, Chuang; Yan, Xingpeng; Yan, Zhiqiang; Zhao, Kai; Yu, Wu; Jiang, Xiaoyu
Abstract: A novel nonuniform sampling method for bandwidth compression of full parallax holographic stereograms is presented. The configuration of the holographic stereograms and the angular-frequency characteristics of the holographic element on the holographic plane are investigated. The sampling angular-frequencies are chosen for each hogel according to their spectral distribution. Sampling and decompression process for low-pass and band-pass hogels are both introduced. The decompressed hogels can reconstruct their angular spectral distributions accurately, which demonstrates that the nonuniform sampling is a lossless method. Simulation experiments are carried out to verify the proposed method. The results indicate that the method can reduce the number of samples to 46.26% of that of the traditional uniform sampling method, and the decompressed holographic stereogram can reconstruct full parallax images of a 3D object with high quality.